The entropy crisis - Deutscher, Guy (World Scientific Pub. Co., 2008)
This book aims to prove that the so-called "energy crisis" is really an entropy crisis. Since energy is conserved, it is clear that a different concept is necessary to discuss meaningfully the problems posed by energy supplies and environmental protection. This book makes this concept, entropy, accessible to a broad, nonspecialized audience.